Detection of naturally occurring alloantibody by an in‐clinic antiglobulin‐enhanced and standard crossmatch gel column test in non‐transfused domestic shorthair cats. (17th December 2018) - Goy‐Thollot, Isabelle; Nectoux, Alexandra; Guidetti, Maryline; Chaprier, Benjamin; Bourgeois, Sarah; Boisvineau, Catherine; Barthélemy, Anthony; Pouzot‐Nevoret, Céline; Giger, Urs
Abstract : Background: Blood typing for the A and B antigens is essential and crossmatching testing is generally recommended before transfusing blood to cats. Objective: To evaluate 2 crossmatch (XM) tests. Animals: Forty‐nine healthy domestic shorthair cats that had not received a blood transfusion. Methods: Prospective study. Blood samples were typed for AB using immunochromatographic and flow cytometric techniques. A gel column (GC) and a feline antiglobulin‐enhanced gel column (AGC) XM tests were used for crossmatching. Results: The population included 34 type A, 13 B, and 2 AB cats, with concordant results (r = 1, P < .005) by flow cytometry and immunochromatographic strip kit. The plasma from type A cats had either no or weak anti‐B alloantibodies. The plasma of 12 of 13 type B cats contained strong anti‐A alloantibodies. For crossmatching, plasma to RBC pairings were prepared using the GC (n = 446) and AGC (n = 630) tests. Both methods showed compatibilities in 329 and incompatibilities in 102 pairings including all A‐B mismatches. Additionally 15 pairings showed agglutination by the AGC but not GC method. Fourteen incompatibilities outside the expected A‐B mismatches were only revealed by AGC. Conclusions and Clinical Importance: AB typing using immunochromatographic strip is as accurate as laboratory flow cytometry. The 2 XM methods had good agreement with additional incompatibilities being recognized by the AGC XM beyond A‐B incompatibilities. In clinic, feline AB typing and sensitive XM test kits are available and recommended before each transfusion, although the clinical implications of incompatible XM test results and clinical benefits of such crossmatching have not been documented.